The Effect of Broiler Breeder Strain and Parent Flock Age on Hatchability and Fertile Hatchability - Abudabos, A. (International Journal of Poultry Science, 2010)
The effect of genetic strain (Ross 308; Cobb 500) and parent flock age (Ross at 32 and 36 weeks; Cobb at 26 and 44 weeks of age) on hatchability, fertile hatchability, Egg Weight Loss (EWL) and egg break out analysis were examined. At each flock age, 300 eggs from each treatment group were incubated. Thirty eggs from each treatment group were labeled individually for the measurements of Egg Weight Loss (EWL) and the newly hatched chicks from all groups were weighed individually. All the eggs that failed to hatch were examined for fertility and determine the embryo death cause. Data were analyzed by ANOVA for a randomized complete block design, using GLM procedure of SAS. Hatchability and fertile hatchability were affected by age of the breeder flock. Egg and chick weight were influenced by hen age (p<0.001), the older the hen the heavier the egg. Total egg weight loss from 1-19 d was significantly higher as percent for Cobb strain (p<0.001). Mid death of embryos as well as pips percentages were associated with eggs from older hens (p<0.01). In summary, hatching eggs produced by older broiler breeders have been shown to be larger in size and they also exhibit a reduced fertility. It is evident that egg management and incubation procedures need to be altered, as current recommended egg management and incubation procedures are not adjusted for breeder age.